Beyond Sulfate-Free Personal Cleansing Technology - Evelyn Su; Stephen Herman (Cosmetics)
There is a strong global demand for sulfate-free personal cleansing products. The objective of sulfate-free personal cleansing technology should not be aimed solely at the absence of “sulfate” wording in the list of ingredients, but on the true benefits both in personal use and in environmental effects. These include but are not limited to safety, mildness, and sensory effect for the individual and renewability, low carbon footprint, low water footprint, biodegradability, and sustainability for the environment. In addition, some surfactants or their precursors contain 1,4-dioxane as a by-product of their manufacturing, which is a major safety concern. This paper will deal with sulfate-free cleansing in two parts. Part I will examine the issues surrounding sulfates. Part II will show the benefits of amino acid-based surfactants for cleansing products, and specifically show why glutamates and alaninates are the best choices for safer and more efficacious cleansing. Several metrics will be included to support these conclusions.